Sistema upravleniia korporativnoi kul'turoi - Piskareva M. A. (Scientific dialogue: economics and management)
the article analyzes the main types of organizational culture, its importance and impact on productivity, the main objectives and tasks. Ways of managing corporate culture in the enterprise.
Keywords: коллектив; персонал; эффективность; корпоративная культура; труд; трудовые отношения; efficiency; personnel; labor relations; Key words: corporate culture; team work